Pendampingan Keterampilan Proses Sains Anak TPA St.Giulia Salzano School Maumere Kolaborasi Eksperimen STEAM Loose Part dan Ekologi Bronfenbrenner - Nirmalasari, Yohanita; Helvina, Maria; Puang, Desi Maria El; Tuto, Maria Eufrosina; Dalewuk, Maria Costarika (Jurnal SOLMA, 2025)
Background:The science process skill is very important in early childhood. The golden age is a sensitive period for children as it’s a big potential for science learning. Innovation of STEAM loose parts and Bronfenbrenner ecology has a very significant impact on the development of the science process. The aim of this community service is to accompany the science process skill through a child-friendly experiment. Methods: Accompany the direct experiment through preparation, action, and evaluation. The number of samples is twenty to thirty children of TPA St.Giulia Salzano School aged 3-6 years. The instruments of data collection are an observation sheet, anecdote notes, an interview sheet, and a science product. Quantitative data analysis based on percentage calculations of achievement categories and qualitative narratives. Results: The average of the science process skill of children is well developed. These categories are BSB (33, 23 %), BSH (40, 47%), MB (24, 37%) dan BB (1, 92%). Conclusions: Most children have science process skills that develop as expected with only a small group of children yet to develop. Every child has the potential to develop science process skills through science experiments based on a loose-part STEAM environment.